Infant manual performance during reaching and grasping for objects moving in depth - Domellöf, Erik; Barbu-Roth, Marianne; Rönnqvist, Louise; Jacquet, Anne-Yvonne; Fagard, Jacqueline (Frontiers in Psychology, 2015)
Few studies have observed investigated manual asymmetries performance in infants when reaching and grasping for objects moving in directions other than across the fronto-parallel plane. The present preliminary study explored manual object-oriented behavioral strategies and hand side preference in 8- and 10-month-old infants during reaching and grasping for objects approaching in depth from three positions (midline, and 27° diagonally from the left, and right, midline). Effects of task constraint by using objects of three different types and two sizes were further examined for behavioral strategies and . The study also involved measurements of hand position opening prior to grasping., and Additionally, assessments of general hand preference by a dedicated handedness test were performed. Regardless of object starting position, the 8-month-old infants predominantly displayed right-handed reaches for objects approaching in depth. In contrast, the older infants showed more varied strategies and performed more ipsilateral reaches in correspondence with the side of the approaching object. Conversely, 10-month-old infants were more successful than the younger infants in grasping the objects, independent of object starting position. The findings support the possibility of a shared underlying mechanism regarding for infant hand use strategies when reaching and grasping for horizontally objects moving in depth are similar to those from earlier studies using objects moving along a horizontal pathand vertically moving objects. Still, initiation times of reaching onset were generally long in the present study, indicating that the object motion paths seemingly affected how the infants perceived the intrinsic properties and spatial locations of the objects, possibly with an effect on motor planning. Findings are further discussed in relation to future investigations of infant reaching and grasping for objects approaching in depth.